Omanization:: A Three Tier Strategic Framework for Human Resource Management and Training in the Sultanate of Oman. - Al-lamki, Salma (Journal of Comparative International Management)

(untitled) (Management Futures, 2000)
This paper addresses the issue of Human Resource Management (HRM) and training with particular emphasis on Omanization (the replacement of expatriate with Omanies) in the Sultanate of Oman. First, the paper discussess an overview of the human resource management practices in the Gulf Cooperation Council (GCC) countries and the emerging economies of East Asia. This is followed by the specifics of the Sultanate of Oman's experience outlining the national policies on human resource management & training and government supported Omanization schemes and incentives. Finally, the author recommends an integrated and holistic three tier strategic framework for human resource management and training in the Sultanate of Oman.